2007
DOI: 10.1080/08977190701838402
|View full text |Cite
|
Sign up to set email alerts
|

IGF-I in epithelial ovarian cancer and its role in disease progression

Abstract: Insulin-like growth factor-I (IGF-I) is known to be involved in the development and progression of several types of solid tumors including ovarian cancer. IGF-I levels in local tissue is subject to both endocrine and paracrine/autocrine regulation. To investigate which regulation is more importantly involved in IGF-I action in ovarian cancer regarding tumor progression, we analyzed IGF-I mRNA expression (assuming only from paracrine/autocrine regulation) and peptide concentration (subject to both endocrine and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
50
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 31 publications
5
50
1
Order By: Relevance
“…In addition, not all factors which influence the regulation of serum IGF-1 have been fully elucidated. However, based on our results and the available literature, it seems safe to conclude that the level of IGF-1 in OC tissues is probably affected by endocrine and autocrine regulation, which is consistent with the results obtained by Brokow and Conover [6,38]. Studies conducted to clarify the role of IGF-1 (both, locally synthesized and peripherally circulating serum) in the biology of breast cancer, have confirmed the role of this factor in the oncogenesis of this tumor [35].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In addition, not all factors which influence the regulation of serum IGF-1 have been fully elucidated. However, based on our results and the available literature, it seems safe to conclude that the level of IGF-1 in OC tissues is probably affected by endocrine and autocrine regulation, which is consistent with the results obtained by Brokow and Conover [6,38]. Studies conducted to clarify the role of IGF-1 (both, locally synthesized and peripherally circulating serum) in the biology of breast cancer, have confirmed the role of this factor in the oncogenesis of this tumor [35].…”
Section: Discussionsupporting
confidence: 82%
“…Both, in vitro and in vivo studies indicate that the local IGF-1 system is involved in the induction of tumor cell proliferation, invasion and neoangiogenesis [2][3][4][5]. Various sources have reported IGF-1 overexpression in both, tumor tissues of OC and tumor-derived fluid [6][7][8][9]. Researchers, inspired by the results of OC cell and tissue tests, started to investigate serum IGF-1 in women with OC.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical findings implicated IGF1 in the induction of cell proliferation and invasion (Cao et al 2007, Lau & Leung 2012. Furthermore, the positive effect of IGF1 on ovarian cancer progression was supported by the correlation of increased IGF1 expression in cancer tissues with disease progression (Brokaw et al 2007) or poor prognosis (Spentzos et al 2007). Similarly, IGF2 gene expression was found to be increased in tumors with poor prognosis (Sayer et al 2005, Lu et al 2006 and to be an independent predictor of poor survival (Sayer et al 2005).…”
Section: Discussionmentioning
confidence: 74%
“…To test this, we examined a set of inhibitors at effective concentrations that specifically inhibit various RTKs, including general RTKs (genistein), IGF-1R (AG1024), fibroblast growth factor receptor 1 (SU5402), epidermal growth factor receptor (EGFR) (AG1478) and hepatocyte growth factor receptor c-Met (K252a), which have been previously implicated in the progression and metastasis of ovarian cancer (Ellerbroek et al, 2001;Steele et al, 2001;Brokaw et al, 2007;Sawada et al, 2007). Among these inhibitors, we found that only genistein used to block RTK or AG1024 used to inhibit IGF-1R led to a marked decrease in p120 ctn activation ( Figure 3a) and translocation ( Figure 3b) following GnRHa stimulation.…”
Section: Resultsmentioning
confidence: 99%